2018
DOI: 10.1099/mic.0.000608
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of two Lactobacillus strains during infection with Gardnerella vaginalis and Candida albicans in a HeLa cell culture model

Abstract: Lactobacilli are the dominant bacteria of the vaginal tract of healthy women and they play a major role in the maintenance of mucosal homeostasis, preventing genital infections, such as bacterial vaginosis (BV) and vulvovaginal candidiasis (VVC). It is now known that one mechanism of this protection is the influence that lactobacilli can exert on host immune responses. In this context, we evaluated two Lactobacillus strains (L. plantarum 59 and L. fermentum 137) for their immunomodulatory properties in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…In this study, incubation of vaginal epithelial cells with G. vaginalis alone caused significant upregulation of multiple inflammatory cytokines (IL-6, IL-8, IL-1α, MIP-1α, MIP-1β and MIP-3α), while pre-incubation with lactobacilli resulted in significant downregulation of IL-6 and IL-8 and nonsignificant downregulation of each of the chemokines evaluated. These findings are similar to previous studies showing that G. vaginalis induces inflammatory responses both in vitro and in vivo and lactobacilli have immunoregulatory properties in vitro and are associated with low inflammatory cytokine levels in vivo 28,32,33 . Although the majority of inflammatory cytokines and chemokines were lower following pre-incubation with lactobacilli prior to incubation with G. vaginalis, we found that IL-1α and IL-1β production was significantly higher compared to G. vaginalis and Lactobacillus only cultures.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, incubation of vaginal epithelial cells with G. vaginalis alone caused significant upregulation of multiple inflammatory cytokines (IL-6, IL-8, IL-1α, MIP-1α, MIP-1β and MIP-3α), while pre-incubation with lactobacilli resulted in significant downregulation of IL-6 and IL-8 and nonsignificant downregulation of each of the chemokines evaluated. These findings are similar to previous studies showing that G. vaginalis induces inflammatory responses both in vitro and in vivo and lactobacilli have immunoregulatory properties in vitro and are associated with low inflammatory cytokine levels in vivo 28,32,33 . Although the majority of inflammatory cytokines and chemokines were lower following pre-incubation with lactobacilli prior to incubation with G. vaginalis, we found that IL-1α and IL-1β production was significantly higher compared to G. vaginalis and Lactobacillus only cultures.…”
Section: Discussionsupporting
confidence: 92%
“…disorders [31][32][33][34] . L. rhamnosus (4B15) and L. gasseri (4M13) have been reported to have antioxidative activity, inhibit α-glucosidase activity, reduce cholesterol, and suppress NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Genital inflammation, driven by a highly diverse vaginal microbiota, and increased cervicovaginal levels of proinflammatory cytokines and chemokines are associated with higher levels of HIV transmission (Masson et al, 2015;Gosmann et al, 2017). Beneficial vaginal lactobacilli (e.g., L. crispatus) dampen inflammatory and inhibit pro-inflammatory responses mediated by TLR agonists (Rose et al, 2012;Doerflinger et al, 2014) and vaginal pathogens (Santos et al, 2018), and we have demonstrated that this effect is mediated, at least in part, by LA (Hearps et al, 2017). Here, we asked whether this effect is maintained in the presence of physiological concentrations of other vaginal organic acid metabolites.…”
Section: A Eubiotic Vaginal Microbiota Metabolite Mixture Containing mentioning
confidence: 99%